Cloning of red snapper (Lutjanus argentimaculatus) growth hormone cDNA and mRNA expression during early development. - Samentar, Lorena P.
Growth hormone regulates growth and development in vertebrates. As a first step to understand the role of growth hormone in the regulation of growth and development of snapper, the snapper growth hormone (sGH) cDNA was cloned using reverse transcription - polymerase chain reaction (RT-PCR) and rapid amplification of cDNA ends, and the expressions of sGH mRNA in embryos and larvae was examined also by RT-PCR. Excluding the poly-A tail, the full-length snapper GH cDNA is 945 base pairs (bp) long. It contains untranslated regions of 99 bp and 234 bp in the 5' and 3' ends, respectively. It has an open reading frame of 612 bp coding for a signal peptide of 17 amino acids and a mature hormone of 187 amino acid residue. Snapper GH contains 4 cysteine residues and the typical polyadenylation site 16 bp upstream of the poly-A tail. Based on the amino acid sequence of the mature hormone, sGH shows higher sequence identity (>75%) to GHs of perciforms like grouper, seabream, tuna, seabass, tilapia and rabbitfish than to GHs salmonids, carps and milkfish. Sequence identity with GHs of more primitive fishes and other vertebrates belonging to a different class is low. Semi-quantitativ RT-PCR showed that expressions of sGH mRNA commenced two days after hatching.